An IRAK1–PIN1 signalling axis drives intrinsic tumour resistance to radiation therapy - Liu, Peter H.; Shah, Richa B.; Li, Yuanyuan; Arora, Arshi; Ung, Peter Man-Un; Raman, Renuka; Gorbatenko, Andrej; Kozono, Shingo; Zhou, Xiao Zhen; Brechin, Vincent; Barbaro, John M.; Thompson, Ruth; et al. (Nature cell biology, 2019)
Drug-based strategies to overcome tumour resistance to radiotherapy (R-RT) remain limited by the single-agent toxicity of traditional radiosensitizers (for example, platinums) and a lack of targeted alternatives. In a screen for compounds that restore radiosensitivity in p53 mutant zebrafish while tolerated in non-irradiated wild-type animals, we identified the benzimidazole anthelmintic oxfendazole. Surprisingly, oxfendazole acts via the inhibition of IRAK1, a kinase thus far implicated in interleukin-1 receptor (IL-1R) and Toll-like receptor (TLR) immune responses. IRAK1 drives R-RT in a pathway involving IRAK4 and TRAF6 but not the IL-1R/TLR–IRAK adaptor MyD88. Rather than stimulating nuclear factor-κB, radiation-activated IRAK1 prevented apoptosis mediated by the PIDDosome complex (comprising PIDD, RAIDD and caspase-2). Countering this pathway with IRAK1 inhibitors suppressed R-RT in tumour models derived from cancers in which TP53 mutations predict R-RT. Moreover, IRAK1 inhibitors synergized with inhibitors of PIN1, a prolyl isomerase essential for IRAK1 activation in response to pathogens and, as shown here, in response to ionizing radiation. These data identify an IRAK1 radiation-response pathway as a rational chemoradiation therapy target. Performing a small-molecule screen, Liu et al. identify IRAK as a regulator of PIDDosome activity and tumour radioresistance, and demonstrate a synergistic effect of targeting IRAK1 and PIN1 in response to ionizing radiation.